Role of laparoscopy in evaluation of chronic pelvic pain - Hebbar Shripad; Chawla Chander (Journal of Minimal Access Surgery, 2005)
Introduction: Chronic pelvic pain (CPP) is a common medical problem affecting women. Too often the physical signs are not specific. This study aims at determining the accuracy of diagnostic laparoscopy over clinical pelvic examination. Settings and Design: A retrospective study of patients who underwent diagnostic laparoscopy for CPP. Materials and Methods: The medical records of 86 women who underwent laparoscopic evaluation for CPP of at least 6-month duration were reviewed for presentation of symptoms, pelvic examination findings at the admission, operative findings and follow up when available. Statistical analysis used: McNemar Chi-square test for frequencies in a 2 x 2 table. Results: The most common presentation was acyclic lower abdominal pain (79.1%), followed by congestive dysmenorrhoea (26.7%). 61.6% of women did not reveal any significant signs on pelvic examination. Pelvic tenderness was elicited in 27.9%. Diagnostic laparoscopy revealed significant pelvic pathology in 58% of those who essentially had normal pervaginal findings. The most common pelvic pathology by laparoscopy was pelvic adhesions (20.9%), followed by pelvic congestion (18.6%). Laparoscopic adhesiolyis achieved pain relief only in one-third of the women. Conclusion: The study revealed very low incidence of endometriosis (4.7%). Overall clinical examination could detect abnormality in only 38% of women, where as laparoscopy could detect significant pathology in 66% of women with CPP. This shows superiority of diagnostic laparoscopy over clinical examination in detection of aetiology in women with CPP (P < 0.001). Adhesiolysis helps only small proportion of women in achieving pain control.